Meningkatkan Hasil Belajar Siswa Pada Masa Covid-19 Melalui Zoom Meeting di MTs Jam’iyah Mahmudiyah - Syahfitri, Diani; Sabariah, Hayatun; Arif, Muhammad (Ta'dib: Jurnal Pemikiran Pendidikan, 2022)
Efforts to improve connected skills through Zoom Meeting learning models for MTs students. Jam’iyah Mahmudiyah Private. 1). Grade IX MTs students. Jam’iyah Mahmudiyah Private who obtain learning by using the Zoom Meeting learning model approach shows that the understanding of the Qur'anic material of the Hadith is significantly better than that of students who get regular learning. This can be seen from the average score of the connected ability of students in the study of the Qur'anic Hadith; 2). Connected ability of IX grade MTs students. Jam’iyah Mahmudiyah Private can be done by applying the Learning Zoom Meeting model; 3). There is a significant relationship between the improvement of connected skills through the Learning Zoom Meeting model in MTs. Jam’iyah Mahmudiyah Private. 4). The attitude of students during the learning of the Qur'an the Hadith looks good, namely students have the enthusiasm to participate in classroom learning activities, students look more enthusiastic in learning and communication activities that occur during the learning process in the classroom runs effectively, as the communication runs two directions, namely from teacher to student and vice versa from students to teachers; 5). Activities of students who get learning using learning models Zoom Meeting is more active in learning in class and students who get the application of learning models Zoom Meeting is more active in improving students' connected skills, and also students are more daring to ask or ask questions to teachers, and be more creative in solve the problem given, so the connected ability of MTs students. Jam’iyah Mahmudiyah Private can be improved through the application of the Zoom Meeting model.